Clinical Features and Therapeutic Effects of Anti-leucine-rich Glioma Inactivated 1 Encephalitis: A Systematic Review - Teng, Yuou; Li, Ting; Yang, Zhizhong; Su, Mingwan; Ni, Jingnian; Wei, Mingqing; Shi, Jing; Tian, Jinzhou (Frontiers in Neurology, 2022)
Background Clinical presentations and treatment programs about anti-leucine rich glioma inactivated 1 (LGI1) encephalitis still remain incompletely understood. Objective This study analyzed the clinical features and therapeutic effects of anti-LGI1 encephalitis. Methods PubMed, EMBASE, and the Cochrane Library were searched to identify published English and Chinses articles until April 2021. Data was extracted, analyzed and recorded in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Results A total of 80 publications detailing 485 subjects matched our inclusion criteria. Short-term memory loss (75.22%), faciobrachial dystonic seizures (FBDS) (52.53%), other seizures excluding FBDS (68.48%), psychiatric symptoms (57.67%), and sleep disturbances (34.30%) were the most frequently described symptoms in anti-LGI1 encephalitis. Hyponatremia (54.90%) was the most common hematologic examination change. The risk of incidence rate of malignant tumor was higher than healthy people. Positive rate of anti-LGI1 in serum (99.79%) was higher than CSF (77.38%). Steroids（93.02%）, IVIG（87.50%） and combined use（96.67%）all had a high remission rate in initial visit. 35 of 215 cases relapsed, of which 6/35 (17.14%) didn’t use first-line treatment, and 21 (60.00%) didn’t maintain long-time treatment. Plasma exchange (PE) could be combined in severe patients, immunosuppressant could be used when refractory or recurrence and using anti-epileptic drug to control seizures may benefit for cognition. Conclusions Short-term memory loss, FBDS, psychiatric symptoms and hyponatremia were key features in identify anti-LGI1 encephalitis. Serum and CSF antibody test should be considered in diagnosis criteria. Steroids with IVIG should be recommended, PE was combined to use in severe patients, immunosuppressant therapy might improve outcomes if recurrence or progression occurred, and control seizures might benefit for cognition. The useful way to reduce relapse rate were early identified, clear diagnosis, rapid treatment, and maintain long-time treatment. The follow-up advice was suggested according to the research of paraneoplastic syndrome, and concern about tumor was vital as well.